Admission conditions and graduates' employability - Fernando Alexandre; Miguel Portela; Carla Sá (Institute for the Study of Labor (IZA), 2008)
We evaluate the information content of admission conditions for study programs' quality by investigating its relationship with graduates' employability. We find that study programs with larger numeri clausi are associated with a higher probability of finding a job. Additionally, compulsory admission exams seem to be informative about study programs' quality. Namely, study programs requiring the Math exam appear to be linked with lower unemployment propensity. Cardoso et al. (2008), however, found that those programs face lower demand when compared to other studies. These paradoxical results suggest that students' choices may be based on insufficient information on returns to higher education investment. That information failure indicates that a Government intervention may be due.
urn:nbn:de:101:1-20080609115
Keywords: C21; 330; Higher education; unemployment propensity; fractional models; Studium; Berufswahl; Bildungschancen; Beschäftigungsfähigkeit; Arbeitslosigkeit; Bildungsertrag; Portugal